Microstructure modification and improving corrosion resistance of laser surface quenched nickel–aluminum bronze alloy. (September 2020) - Qin, Zhenbo; Xia, Da-Hai; Zhang, Yiwen; Wu, Zhong; Liu, Lei; Lv, Yuting; Liu, Yichun; Hu, Wenbin
Graphical abstract: A supersaturated solid solution layer with a fine-grained size of 30–50 μm was formed on a nickel–aluminum bronze via laser surface quenching technology, and its corrosion resistance was improved by 42.6%, which was attributed to the homogenized element distribution and the formation of a more protective film during corrosion process. Highlights: The microstructure of as-cast NiAl bronze was refined by laser surface quenching. Selective phase corrosion was eliminated for the uniform element redistribution. Corrosion rate decreased 42.6% after laser surface quenching. Enhanced corrosion resistance was ascribed to formation of a more protective film. Abstract: Laser surface quenching technology was utilized to modify the surface microstructure of as-cast nickel-aluminum bronze. A supersaturated solid solution layer with a fine-grained size of 30–50 μm was formed, and its corrosion behavior was studied by electrochemical measurements and long-term immersion corrosion test. It was found that laser surface quenching homogenized the distribution of elements in the constituent phases and eliminated the selective phase corrosion. Due to the formation of a more protective film on laser quenched NAB alloy, the corrosion rate reduced about 42.6% compared with that of as-cast NAB alloy.